Mental health and substance use in urban left-behind children in China: A growing problem. (September 2020) - Wang, Feng; Lin, Leesa; Lu, Jingjing; Cai, Jingjing; Xu, Jiayao; Zhou, Xudong
Highlights: Urban left-behind children showed higher mental health disorders than urban children. Urban left-behind children showed more substance use than urban children. Urban left-behind children even worse than rural left-behind children. Parent-child communication and resilience were associated factors. Abstract: Children left behind by their migrant parents in urban and rural areas represent two vulnerable but distinct populations that have emerged due to the large-scale population migrations that occur within China. In 2015, there were an estimated 28 million urban left-behind children and around 41 million rural left-behind children. The purpose of this study was to examine the mental health status and substance use behaviors of urban left-behind children and urban children still living with their parents in comparison to rural left-behind children. This study also sought to investigate how parent-adolescent communication and children's resilience may moderate or exacerbate mental health status and/or substance use across children experiencing different forms of parental migration and hukou status (household registration system), using cross-sectional data from a school-based questionnaire survey with a sample of 4565 children living in both urban and rural counties of Anhui province. Regression model results suggest that, compared to urban children who lived with both parents, urban children who were currently left-behind appeared to exhibit higher mental health difficulties (emotional symptoms and total difficulties) and more substance use (smoking and drinking). Urban left-behind children were also found to experience more mental health problems and substance use than rural left-behind children. Our results indicated that both parent-adolescent communication and resilience were strongly associated with children's mental health and substance use outcomes. These findings have significance for the creation and tailoring of interventions directed at urban left-behind children.